2009
DOI: 10.1289/ehp.0901002
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis: A Conversation with a Critic

Abstract: ObjectiveIn this commentary I respond to points raised in the commentary by Mushak [Ad hoc and fast forward: the science and control of hormesis growth and development. Environ Health Perspect 117:1333–1338 (2009)], which principally concerns studies by me and my colleagues concerning the frequency of hormesis in toxicology.DiscussionIn this commentary I demonstrate that Mushak’s analysis contains critical statistical errors and misunderstandings of statistical concepts that invalidate its conclusions concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…The detection of this phenomenon, called hormesis in toxicology, is a novel result when working with soil microbial communities exposed to glyphosate. Although hormesis has been extensively reviewed (Calabrese, 2005(Calabrese, , 2009Duke et al, 2006), there are scarce reports related to glyphosate and it was only observed in cultured microbes exposed to the herbicide (Qiu et al, 2012;Nweke et al, 2014). A possible explanation for the observed hormesis could be the increase in respiration response at low doses due to sarcosine catabolism (a product derived from the biodegradation of glyphosate) in addition to the respiration of coumaric acid inoculated in the plate.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of this phenomenon, called hormesis in toxicology, is a novel result when working with soil microbial communities exposed to glyphosate. Although hormesis has been extensively reviewed (Calabrese, 2005(Calabrese, , 2009Duke et al, 2006), there are scarce reports related to glyphosate and it was only observed in cultured microbes exposed to the herbicide (Qiu et al, 2012;Nweke et al, 2014). A possible explanation for the observed hormesis could be the increase in respiration response at low doses due to sarcosine catabolism (a product derived from the biodegradation of glyphosate) in addition to the respiration of coumaric acid inoculated in the plate.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with Science and Technology Innovation Base, Guilin University of Technology, Guilin 541004, China. 4 Technical Innovation Center for Mine Geological Environment Restoration Engineering in Shishan Area of South China, Ministry of Natural Resources, Nanning 530028, China.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The toxicity of pollutants in realistic environment is controlled not only by their concentration or dosage, but also by their exposure time. Under long-term exposure conditions, low-dose pollutants may exhibit the so-called hormetic effect [1][2][3][4][5][6]. This phenomenon implies that high-concentration chemicals show an inhibition effect on organisms, while low-concentration ones have a stimulation effect [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In my commentary (Calabrese 2009), I addressed and/or rebutted in considerable detail his arguments (Mushak 2009), and no new data require me to revise that response. Here I address the key areas raised by Mushak’s letter, two of which relate to the frequency of hormesis, and the third considers the acceptance of hormesis by the scientific and regulatory communities.…”
mentioning
confidence: 99%